Laboratory coagulation tests and emicizumab treatment A United Kingdom Haemophilia Centre Doctors' Organisation guideline. Issue 1 (20th December 2019) - Jenkins, P. Vincent; Bowyer, Annette; Burgess, Clive; Gray, Elaine; Kitchen, Steve; Murphy, Paul; Platton, Sean; Riddell, Anne; Chowdary, Pratima; Lester, Will
Abstract: Introduction: The factor VIII mimetic emicizumab (Hemlibra, Hoffman‐la Roche, Basel, Switzerland) has a novel mode of action that affects the laboratory monitoring of patients receiving this treatment. Aim: This guideline from the United Kingdom Haemophilia Centre Doctors Organisation (UKHCDO) aims to provide advice for clinical and laboratory staff on appropriate use of laboratory assays in patients with Haemophilia A treated with emicizumab. Methodology: The guideline was prepared by a review of the available literature and discussion and revision by the authors. Results: The guideline describes the effect of emicizumab on commonly used coagulations tests and provides recommendations on the use of assays for measurement of factor VIII and factor VIII inhibitor in the presence of emicizumab. The guideline also provides recommendations on measurement of emicizumab. Conclusion: Knowledge of the effect of emicizumab on coagulation tests and factor assays is required to ensure appropriate testing and monitoring of therapy in patients receiving this drug.